The Golden Age of Polish Philosophy
X, 254 p.
Keywords: This volume portrays the Polish or Lvov-Warsaw School, one of the most influential schools in analytic philosophy, which, as discussed in the thorough introduction, presented an alternative "working" picture of the unity of science. The school was founded by a phenomenologist, Kazimierz Twardowski, who trained a team of researchers that included some of the most important logicians and philosophers of the history of analytical philosophy, such as Tarski, Lesniewski and Lukasiewicz. The Polish School represented some of the most important trends in philosophy -- aristotelism; the history and philosophy of science; linguistics; the philosophy of logic and mathematics -- and offered an opportunity for all these philosophical disciplines to interact in a natural and fruitful way.